2019
DOI: 10.1080/2162402x.2019.1638210
|View full text |Cite
|
Sign up to set email alerts
|

Immunological monitoring of newly diagnosed CML patients treated with bosutinib or imatinib first-line

Abstract: Changes in the immune system induced by tyrosine kinase inhibitors (TKI) have been shown to positively correlate with therapy responses in chronic myeloid leukemia (CML). However, only a few longitudinal studies exist and no randomized comparisons between two TKIs have been reported. Therefore, we prospectively analyzed the immune system of newly diagnosed CML patients treated with imatinib (n = 20) or bosutinib (n = 13), that participated in the randomized BFORE trial (NCT02130557). Comprehensive immunophenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…22 The mechanism of action for bosutinib is unclear; however, major TA B L E 7 Management of cardiac, vascular, hypertension, and effusion TEAEs immunological changes during treatment do not seem to be the predominant factor. 23 Although nilotinib treatment has been associated with fluid-retention AEs, such as peripheral edema, the incidence of pleural effusion is relatively low (~1-2%). 24 This study determined age ≥ 65 years, ECOG PS > 0, a history of hyperlipidemia, and a history of cardiac disorders were prognostic risk factors of cardiac AEs and history of vascular disorders to be prognostic of vascular AEs with bosutinib treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The mechanism of action for bosutinib is unclear; however, major TA B L E 7 Management of cardiac, vascular, hypertension, and effusion TEAEs immunological changes during treatment do not seem to be the predominant factor. 23 Although nilotinib treatment has been associated with fluid-retention AEs, such as peripheral edema, the incidence of pleural effusion is relatively low (~1-2%). 24 This study determined age ≥ 65 years, ECOG PS > 0, a history of hyperlipidemia, and a history of cardiac disorders were prognostic risk factors of cardiac AEs and history of vascular disorders to be prognostic of vascular AEs with bosutinib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action with dasatinib has been associated with increase of lymphocytes, specifically natural killer cells 22 . The mechanism of action for bosutinib is unclear; however, major immunological changes during treatment do not seem to be the predominant factor 23 . Although nilotinib treatment has been associated with fluid‐retention AEs, such as peripheral edema, the incidence of pleural effusion is relatively low (~1‐2%) 24 …”
Section: Discussionmentioning
confidence: 99%
“… 77 , 81 , 82 Conversely, immune suppressor cells such as regulatory T-cells (Tregs) and myeloid-derived suppressor cells (MDSCs) expand during disease progression or relapse and are reduced following TKI therapy. 77 , 80 Other immunological factors, such as dendritic cells (DCs), 83 plasmacytoid dendritic cells (pDCs), 84 CD8 + cytotoxic T-cells (CTLs), 85 leukemia-associated antigens (LAAs), 86 and B-cells, 87 also play a pivotal role in contributing to CML; however, further investigation should be launched to explore their impact on therapy responses. Additionally, studies have also indicated that imatinib and dasatinib treatment generates a more active immune system, and changes were not observed during bosutinib treatment.…”
Section: What Is a Better Methods Of Management?mentioning
confidence: 99%
“…Furthermore, imatinib and dasatinib impair CD8+ CTLs specifically directed against LAA function in vitro [ 19 , 20 ], and dasatinib also inhibits NK cell function [ 21 ]. In contrast to the in vitro results, clinical data showed that imatinib or dasatinib treated patients exhibit expansion of CD8+ CTLs or NK cells which are associated with an improved response to therapy [ 22 24 ]. Furthermore, dasatinib may induce a reversible state of aberrant immune reactivity, leading to large granular lymphocytic lymphocytosis, which is associated with a favorable clinical response [ 22 ].…”
Section: An Overview Of Immunological Profile In CML and Effects Of Tki Treatmentmentioning
confidence: 99%